TLC - Colombia - South Korea: Characteristics and results for Colombia during the period 2016-2018 (2019)
The free trade agreement signed between South Korea and Colombia since 2013 and which came into force in July 2016, is part of the economic policy in force in the country since the early 1990s. The opening to economic globalization it is a reality to which no country considered in development can be foreign and for that reason in the Colombian case it is a necessary risk due to the need to open its borders to participate in the global dynamics of trade. Colombia has the experience of treaties with other economically strong nations such as the United States. The results achieved continue to be controversial between different sectors of national and economic life due to the impacts that are already visible in productive sectors and the experiences of others. nations of the continent, who with the passage of time and the development of agreements that in principle generate an increasing demand for new products, then resent as their economies that are less strong, are affected by the stagnation or loss of their industrial resources, employment and the decrease in purchasing power. The search for an agreement with South Korea proposed a turn in the dynamics of opening for Colombia with the entry into the Asian market, which is recognized as the best projection in the coming decades, however, the transactional conditions and primary results of the treaty reached with the Koreans, does not suppose advantages or achievements different from those reached with other treaties.